Analysis on the effect of different elevation cut-off angles on GPS time transfer. (December 2021) - Manandhar, Shilpa; Meng, Yu Song
Abstract: Precise Point Positioning (PPP) based Global Positioning System (GPS) frequency and time transfer methods have proved to achieve good accuracy over past years. Several factors can make significant influence in the realization of an accurate time transfer, where multipath error is one of the most important. The multipath can be caused by various man-made and natural structures. Also, the longer the propagation distance, the more serious is the effect. This error can be studied with respect to the satellite elevation angles to the ground station. In this paper, the GPS-PPP processed time transfer results are analysed for a varying range of elevation angles. Acceptable accuracy is obtained for an elevation angle of 20° for which 7–8 GPS satellites are visible on average. With the advancement in other Global Navigation System Satellites (GNSS), the number of visible satellites increases, which gives flexibility to filter satellites based on the signal strength quality as well.